Streptococcus Pneumoniae Urinary Tract Infection in 3-Year-Old Girl - Lubarsky, Daniel (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Streptococcus pneumonia is a gram-positive bacteria most commonly associated with respiratory tract infections such as acute otitis media, sinusitis, and pneumonia. While a common cause of upper respiratory infections, the current Infectious Diseases Society of America (IDSA) guidelines on Urinary Tract Infections (UTIs) do not cite S. pneumoniae as a cause for UTIs in children. In addition, previous research associating S. pneumonia with UTIs has been scarce. We report the case of a three-year-old girl presenting to the emergency room with abdominal pain, vomiting, and fever. Her clinical picture was consistent with right sided pyelonephritis. A urine analysis (UA) was conducted which showed trace leukocyte esterase, 150mg/dL ketones, 21-50 WBCs, and negative nitrites. A blood culture returned positive for Streptococcus pneumoniae along with right kidney hydronephrosis on ultrasound. This patient presented with a full clinical picture of pyelonephritis, fever, leukocytosis, elevated CRP and Procalcitonin levels, and later found to be S. pneumoniae positive. Although the urine culture did not grow any definitive single bacteria as a causative agent, due to the presentation of pyelonephritis along with CVA tenderness, dysuria, and a positive blood culture, we conclude the patient was exhibiting urosepsis due to S. pneumoniae. Upon discovering previous case reports noting S. pneumoniae as a possible agent for UTIs, we believed this bacterium to be contributing to the patient’s symptoms. While S. pneumoniae has only been a rarely reported cause of UTIs, we believe there is sufficient evidence that demonstrates S. pneumoniae to at least be considered a possible contributing cause of UTIs, especially if the patient has a coinciding septic picture. Contributors: Daniel Lubarsky (a) (1) Daniel Garcia (b) and Deepa Mukundan (c) (a) M.D. Candidate, Class of 2021, The University of Toledo Heath Science Campus, Toledo, OH, USA, (b) Department of Pediatrics, University of Toledo Health Science Campus, Toledo, OH, USA , and (c) Department of Pediatric Infectious Disease, The University of Toledo Heath Science Campus, Toledo, OH, USA